The Islamic Banking Dilemma: Are CEO Turnover And IPO The Right Steps For Islamic Banks In GCC? - Sarif, Reza; Wicaksono, Ahmad Tibrizi Soni (Al-Infaq: Jurnal Ekonomi Islam, 2024)
This research aims to measure banking performance by revealing the influence of CEO changes and IPOs on Islamic banks. Apart from that, this research also involves control variables, namely GDP and inflation, to verify and test the robustness of the findings. This research uses a quantitative approach, measured using a panel data regression-based method with Eviews version 12. The population of this research is Islamic banks in the GCC region for the period 2013 - 2022. The sample was determined based on the purposive sampling method with a total sample of 17 companies, so the total observations in the research are 2040 observations. The data used in this research is secondary data. The data collection technique uses documentation methods via the sites: https://www.ifsb.org/, https://data.worldbank.org/, and the personal banking website. The research results prove that the CEO turnover probability value is 0.035 <0.05 with a t-statistic of -2.102, meaning that CEO turnover has a negative and significant effect on financial performance. The probability value of Initial Public Offering is 0.0002 <0.05 with a t-statistic of 3.766 so it can be concluded that IPO has a significant positive effect on financial performance. Macroeconomic control variables also have a significant effect on financial performance as evidenced by a probability value of 0.000. Meanwhile, the results of the f test show a probability value of 0.000 < 0.05, this result shows that there is a simultaneous influence in this research.